Dermoscopy in superficial fungal infection - Putu Dyah Sawitri; I Gusti Ayu Agung Dwi Karmila; Marrietta Sugiarti Sadeli (Explorer Front, 2021)
Superficial fungal infections are one of the most common skin infection infections. It is caused by fungal pathogens and is limited to the outer layer of the skin, hair, and nails. Superficial fungal infections include dermatophytosis, superficial candidiasis, and diseases caused by Malassezia spp. Most physicians diagnose and treat superficial fungal infections based solely on clinical appearance. But unfortunately, there are many other infectious and non-infectious diseases with a similar clinical appearance. Dermoscopy is a practical and noninvasive imaging method that allows magnifying clinical surface images that are normally invisible under a magnifying lens. In diagnosing superficial mycosis, dermoscopy was more sensitive and specificity than potassium chloride (KOH) and fungal culture. More understanding is needed about the use of dermoscopy in diagnosing superficial fungal infections in the hope of providing an overview of superficial fungal infections and dermoscopy, as well as dermoscopy features in some superficial fungal infections. This article describes dermoscopic findings in various superficial fungal infections on the skin, hair, and nails.